Effect of Additional Shrimp Shell Flour on Characteristics and Acceptance of Cookies - Eliza Eliza; Tiara Andreliska; Muhammad Aji; Heni Sari Wahyuni (Journal of Applied Food and Nutrition, 2022)
The objective of the research was to study analyze the effect of adding shrimp shell flour to the manufacture of cookies on consumer acceptance. Research using this experimental method was conducted at the Food Technology Science Laboratory, Nutrition Department, Poltekkes Palembang and the Lampung State Polytechnic Laboratory from August to November 2021. The consumer acceptance test was carried out on 30 moderately trained panelists to assess cookies which included aspects of color, taste, aroma and texture. The results of consumer acceptance with the Friedman showed that there were no significant differences in aspects of aroma and texture, but there were significant differences in aspects of color and taste. After the acceptance test was carried out, the next step was to do a proximate analysis test on the most preferred formula, namely formula 2, and protein content (13.6%), fats content (18.6%), carbohydrates content (43.2%), water content (3.7%), and ash content (11.7%). The results of the proximate analysis test were compared with SNI 01-2973-1992, from the results of the analysis the product met the quality standard requirements, but the ash content exceeded the SNI standard.